STUDI PERBANDINGAN PENGGUNAAN MESIN PANEN COMBINE HARVESTER DAN POWER THRESER PADA USAHATANI PADI DI KECAMATAN RAMBUTAN KABUPATEN BANYUASIN - Ariyanto, Ariyanto; Batubara, Mustopa Marli; Abubakar, Rafeah (Universitas Muhammadiyah Palembang, 2016)
Comparative Study of Combine Harvesting Machine Use Harvesterdan Power Threser On Rice Farming in Sub Rambutan Banyuasin. This study aims to determine how the comparison of rice production using a combine harvester harvesting machinery and power threser and to know how it compares to income of rice farmers use a combine harvester harvesting machinery and power threser. This research was conducted in the village of Gelebak In the District of Rambutan Banyuasin in April 2016 until June 2016. The method used is a survey method. The sampling method used was stratified random method lopsided (disproportionate stratified random sampling). Data collection method is the method of direct observation and interviews with farmers using the example of a list of statements previously prepared and assisted with data obtained from the institutions that have to do with research. Meode data processing and data analysis used is descriptive quantitative method to address issues first, and to answer the second problem is to use the revenue formula, then testing with Wilcoxon rank test. The results showed that the production of rice farmers who use the machine harvesterberbeda combine real than using the engine power threserdi Village Gelebak In the District of Rambutan Banyuasin and income of rice farmers who use the machine combine real harvesterberbeda of farmers using engine power threserper hectare per season tanam.Pendapatan rice farmers combine engine that uses real harvesterberbeda of farmers using engine power threserper hectare per cropping season.